EKSTRAKSI DAN STABILITAS WARNA UBI JALAR UNGU SEBAGAI PEWARNA ALAMI - Ulya Sarofa dan Dhini Anggrahini, Sri Winarti, (Jurnal Teknik Kimia, 2008)
Use sintetic colouring agent for food and baverage not safe, because in most of sintetic colouringagent contain dagerous metal. Because of that to have need to found natural colouring agent.The potential natural colouring agent is anthocianin from purple potato sweet. Anthocianin wasextracted with mixture organic solvent (water, ethanol and acetic acid) in defference proportion.The purpose of this research is to found the optimum proportion of solvent for extractionanthocianin from purple sweet potato and to know stability colour was extracted. This researchtwo  step : one step was extracted anthocianin with mixture organic solvent water, ethanol andacetic acid (5:1:25; 10:1:20; 15:1:15; 20:1:10 dan 25:1:5). Design in this research is RandomDesign with 1 factor, data from experiment analisis with ANAVA and DMRT. Two step was teststability colouring agent from exchange of pH, sugar solutin, salt solution, temperature heating,time heating and for aplikation to made jelly and agar-agar. The result on one step research showthat the optimum organic solvent for extracted anthocianin was 5:1:25 (water:aceticacid:ethanol), with pH solvent 6,80 and polarity 32,77 was produce highest concentration ofanthocianin 1,3170 mg/100gr. The result on two step research show that anthocianin from purpleKey word: Sweet potato, Extracted, natural colouring agent, Ipomoea batatas L.potato sweet more stable at pH acid that pH basic, stable at sugar solution until 50 %, stable atsalt solution until 8 %, stable at heating until 80 °C, stable at heating until 60 menit, and sable formade jelly and agar-agar.